Three Dimensional CFD Studies of a Solar Chimney: Effect of Geometrical Parameters and Diurnal Variations on Power Generated - Ganguli, Arijit A.; Deshpande, Sagar (Frontiers in Chemical Engineering, 2020)
A pilot scale CFD model of solar chimney has been built and validated with experimental results from the literature. Flow patterns have been shown and a parametric study is carried out for the chimney. It is found that power generated increases exponentially with an increase in chimney height and collector area. When diurnal variations are considered, it is observed that during the night the increase in power generation is nearly a linear function of chimney height and collector diameter. A modified design is suggested to improve the energy efficiency of the solar chimney